Decolonizing Britain: An Exchange. (12th May 2022) - Linstrum, Erik; Ward, Stuart; Ogle, Vanessa; Nasar, Saima; Gopal, Priyamvada
Abstract: Beginning in January 2021, Twentieth Century British History asked a group of scholars to reflect on what decolonization means to the field of British history. Twentieth Century British History co-editor Erik Linstrum (University of Virginia) posed questions over email for three rounds of discussion which concluded in December 2021. Stuart Ward (University of Copenhagen), Vanessa Ogle (University of California, Berkeley), and Saima Nasar (University of Bristol) took part. Priyamvada Gopal (Cambridge University) offered a final comment from the perspective of postcolonial studies. Contributions have been lightly edited but the relatively conversational style and flow of ideas in the original exchange have been preserved.